Measuring customer satisfaction towards service quality of counter at Malacca Municipal Council / Azizah Aini...[et al] - Azizah Aini (Faculty of Business and Management, 2013)
The purpose of this study is to investigate the .customers' satisfaction on service quality towards the municipal councils at several locations in Melaka, wllich are Jasin, Hang Tuah Jaya, Melaka Tengah and Alor Gajah. The customers' satisfaction towards the service quality of counter service can be measured with five important elements of SERVQUAL which are tangibility, reliability, responsiveness, assurance and empathy. The sample was randomly selected from the customers of the local municipal councils at several locations in Melaka, which are Jasin, Hang Tuah Jaya, Melal(a Tengah and Alor Gajah by using probability sampling method. Simple convenience random sampling technique was chosen to select the sample size. The data were analyzed using the Statistical Pacl(age in the Social Science Software (SPSS) version 20.0 to measure the impact of these five independent variables on tIle customers' satisfaction towards the local municipal councils at Melal(a. The total of 120 was distributed and analyzed by tal(ing 30 questionnaires for each location. As a conclusion, from the discrepancy gap between customers' expectation and perception, it showed that customers were slightly dissatisfied with the service quality of counter service at the Melal(a's municipal councils in Jasin, Hang Tuah Jaya, Melal(a Tengah and Alor Gajah. Next, the findings concluded that, even though all of the SERVQUAL elements give an impact towards customers' satisfaction level, 'assurance' is the element that give the greatest impact. As for the further recommendations, the researcher suggested to conduct the research with a larger population sample so that the result will be more generalized and accurate. In addition, the research also should be conducted not only in government sectors but also in private sectors so that a better standard for increasing the customers' satisfaction could be identified.